Gli spazi pubblici e la religione (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Prospettive - 2. Duplice dovere - 3. Questioni I - 4. Questioni II - 5. L’accesso visto da Strasburgo - 6. Poteri pubblici e spazi pubblici - 7. Accesso pluralistico: regola ed eccezione.Public spaces and religionABSTRACT: The essay analyzes the legal issues related to the presence of religion in public spaces. The thesis is that it is necessary to consider the various issues (religious building, religious symbols in public buildings etc.) on the basis of the public character of the space. In this way it becomes possible: a) to compare the various issues; b) identify the tasks of public authorities, which must make spaces available to religion and must not discriminate access to spaces. However, there are exceptions to the rule necessary to protect children in classrooms.